Teachers and students' attitudes toward the use of information and communication technology in their learning experience - De la Pena, Janica Anne L.
Today, we are living in a global village where the world has changed so much and one of the main reasons for this rapid development is with use of Information and Communication Technology or the ICT. Through this rapid development of ICT, some experts state the integration of ICT in education will provide promising expectation for improving the quality of education. Due to this, the researchers come up with the study entitled ?Teachers and Students? Attitudes toward the Use of Information and Communication Technology in Their Learning Experience? the sought to answer the question: What are the attitudes of teachers and students in Iloilo City toward the use of Information and Communication Technology in their learning experience? Which are guided by these objectives: first, the researchers intended to determine if the respondents have favourable or unfavourable attitudes toward the use of ICT. Also, this study aimed to know if there is a relationship between the high school teachers and students? demographic profile (gender and age) and their attitudes toward the use of ICT in their learning experience and if there are any factors influencing it. A total of 20 high school teachers and 120 high school students participated in this study Questionnaires using Likert Scale and open-ended questions were used to assess the high school teachers and students? attitudes towards the use of ICT in their learning experience. Results revealed that: (1) that high school teachers and students have favourable attitude towards the use of ICT in their learning experience; (2) that male respondents have much more favourable attitudes toward the use of ICT in their learning experience compared to the female respondents; (3) high school teachers ranging from the age of 21-30 have a 100% favourable attitude toward the use of ICT while 40% from ages 31-40 have unfavourable attitudes toward the use of ICT in their learning experience; (4) there is a significant difference between the teachers aging from 21-30 years old and 31-40 years old on their attitudes on the ease of use of ICT; (5) teachers aging from 31-40 years old have a less favourable attitude toward the use of ICT in their learning experience for they have a phobia in using ICT in class in fear of breaking something when using it; (6) High school teachers also considered that the use of Internet in class made the use of ICT in their learning experience a success with a percentage 30.2% (16) while the factor of virtual communication between the teachers and students made ICT a failure with a percentage of 37%; (7) factors influencing the high school students attitudes toward the use of ICT in their learning experience, use of computers and tablets in class with a frequency of 30% was the most influential factor that made the use of ICT as success and the factor that they believed made ICT a failure was the use of e-books.